2021
DOI: 10.1002/iroh.202002072
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal assembly patterns of macroinvertebrate metacommunity structure in subtropical wetlands with different hydroperiods

Abstract: Understanding seasonal patterns of assembly mechanisms are key to comprehending the metacommunity dynamics of organisms inhabiting temporary habitats such as wetland macroinvertebrates. However, tests of the seasonal variation in assembly mechanisms of macroinvertebrates in wetlands with differing hydroperiods are rare, especially in the Neotropical region. We tested for seasonal patterns in the metacommunity assembly mechanisms of macroinvertebrates in small subtropical highland wetlands of southern Brazil wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…The macroinvertebrate community composition is affected by environmental and spatial variables, thus presenting temporal changes mainly due to precipitation and temperature changes (Silveira et al, 2006;Pires et al, 2020;Santos, et al, 2020). In our study, PERMANOVA showed a significant difference between samplings (F1,11 = 2.26, p = 0.013).…”
Section: Resultssupporting
confidence: 48%
“…The macroinvertebrate community composition is affected by environmental and spatial variables, thus presenting temporal changes mainly due to precipitation and temperature changes (Silveira et al, 2006;Pires et al, 2020;Santos, et al, 2020). In our study, PERMANOVA showed a significant difference between samplings (F1,11 = 2.26, p = 0.013).…”
Section: Resultssupporting
confidence: 48%
“…Therefore, our experiment should be interpreted as applying to understand the dynamics of a single such colonization cycle. Additionally, even though temporary and semi‐permanent ponds only rarely contain fish, any fish effects we find here may still represent important mechanisms of interaction and dynamics with more general application since permanent ponds are also subject to seasonal colonization dynamics (Pires et al 2021).…”
Section: Methodsmentioning
confidence: 88%
“…Adopting the direct development strategy results in less time to complete development. This can be an adaptation for the high-altitude wetlands, that present shorter hydroperiod and two cycles within a season (Pires et al, 2021), to allow these species to survive in intermittent wetlands by allowing two generations of annual fish to coexist over the course of a single hydrological year (García et al, 2018;, García, Smith, et al, 2019Polačik et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In both regions, the annual precipitation is ~1600 mm; although both regions lack a dry season, rainfall volumes in the colder seasons of the year are larger in the Highlands, while evaporation in the Coastal Plain is higher in the warmer seasons (Alvares et al, 2013) (Table S1). Therefore, natural intermittent wetlands in the Highland Grasslands peak in their flooded areas in the winter and dry out in the late spring and summer, although they may vary in the length of their dry period from 3 to 5 months (Pires et al, 2021). In the Coastal Plain, natural intermittent wetlands are flooded for at least a 8-month time window and dry out in the summer for ~3 months (Lanés et al, 2014).…”
Section: Austrolebias Nubiummentioning
confidence: 99%